Complicated Postoperative Course after Pulmonary Artery Sling Repair and Slide Tracheoplasty - Weber, Angelika; Donner, Birgit; Perez, Marie-Hélène; Di Bernardo, Stefano; Trachsel, Daniel; Sandu, Kishore; Sekarski, Nicole (Frontiers in Pediatrics, 2017)
Pulmonary artery sling is a rare congenital condition in which the left pulmonary artery (LPA) arises from the right pulmonary artery, and then passes between the trachea and the esophagus to reach the left lung, thereby forming a sling around the airway. It is often associated with intrinsic tracheal stenosis due to complete cartilaginous rings. Therapeutic management nowadays consists of one-stage reimplantation of the LPA and tracheoplasty with cardiopulmonary bypass support. Here we present a 7-weeks-old boy with pulmonary artery sling and long-segment distal tracheal stenosis who underwent surgical intervention consisting of reimplantation of the LPA and slide tracheoplasty. Multiple respiratory and cardiovascular complications marked the postoperative course. They consisted of recurrent failed attempts in weaning off mechanical ventilation due to bronchomalacia, left vocal cord paralysis, development of granulation tissue at the anastomosis and restenosis of the trachea and the main stem bronchi requiring balloon dilatation. The patient also developed bilateral pulmonary artery thrombosis and stenosis of the LPA. After a prolonged hospitalization, the patient is doing well without any respiratory symptoms and has a good result on follow-up bronchoscopy 1 year after the initial surgery. The stenosis of the LPA responded well to percutaneous balloon dilatation 12 months after the primary surgery. The case illustrates that even though surgical techniques are improving and are in general associated with a low morbidity and mortality, management of pulmonary artery sling and tracheal stenosis can still be challenging. However, good long-term outcome can be achieved if the initial postoperative phase is overcome.